Who gets included in Collective Impact: A mixed methods study of 10 CI initiatives. Issue 1 (1st January 2022) - Abresch, Chad; Grimm, Brandon; Lyons, Kiara; Maloney, Shannon; Tibbits, Melissa
ABSTRACT: This mixed methods study sought to build knowledge of inclusivity practices among 10 CI initiatives. Analyses across two strands of research revealed two distinct definitions of inclusivity: broad inclusivity, which seeks the participation of everyone; and, representative inclusivity, which seeks individuals affected by the problems being addressed. While several of the initiatives had improved inclusivity practices since adopting CI, only a few were found to be broadly inclusive and most acknowledged operating in intentionally exclusive ways at times. All of the initiatives valued representative inclusivity, but members reported struggling to achieve even minimal levels. Proponents of CI should continue to develop guides for practitioners to help ensure both forms of inclusivity.